Mobile Aplikasi Pencegahan Infeksi Luka Pasca Operasi Fraktur - Wijaya, Ananta Baru; Wahyudi, Andri Setiya; Qona'ah, Arina (Journal of Telenursing (JOTING), 2024)
This study aims to identify the effect of mobile applications on preventing postoperative fracture wound infections. The method used is a systematic review through electronic databases, namely CINAHL, ProQuest, PubMed, Web of Science, and ScienceDirect. The results of the study showed that out of 8 research articles, there were articles that reported how to prevent surgical wound infections by performing wound care, use of antibiotics, hand hygiene, education on nutritional intake, high-risk factors for infection, monitoring pain and abnormal body temperature in patients, fracture type, duration of surgery, surgery time, blood sugar levels, leukocyte counts, the application of mobile applications in fracture surgery patients is useful for remote rehabilitation, chat boxes or consultations with doctors, monitoring by sending photos of wound conditions periodically. In conclusion, mobile applications can be an effective and cost-effective method for postoperative care in orthopedic procedures, preventing surgical wound infections by monitoring signs of surgical wound infections through mobile applications after patients return home from the hospital can be very important to know the signs of postoperative infection. Keywords: Fracture, Surgical wound infection, Mobile applications, Prevention, Postoperative